Mineral beneficiation a concise basic course - Subba Rao, D. V. (CRC Press, 2011)
"Beneficiation of run-of-mine ore is a process of value addition through discarding the unwanted gangue bearing minerals from the wanted minerals. Owing to the mineral beneficiation tangible benefits are saving in freight and handling, loss of metal or values through slag, etc. whereas mineral conservation, environment protection by filling the mine using gangue bearing minerals, energy savings et cetera are intangible benefits. This concise basic book present the rudimental knowledge on mineral beneficiation principles and its unit operations. It explains the defenitions and techniques along with the basic formulas with practical examples. This book is designed for professionals in mining and mineral engineering (Geologists, Mining, Metallurgical and Chemical Engineers). It can be used both as a simple reference guide and as a concise course in mineral beneficiation"-- Provided by publisher.
Keywords: Ore-dressing.; elektronické knihy; electronic books